(untitled) (American Journal of Business Management, Economics and Banking, 2026)
Water supply infrastructure is increasingly under pressure due to climate change, rapid urbanization, and rising demand for clean water. Traditional public financing sources are often insufficient to support large-scale modernization of water systems, especially in emerging economies. In response, green finance has emerged as a strategic tool for mobilizing capital toward environmentally sustainable infrastructure development.This paper analyzes green financing opportunities in water supply infrastructure projects, focusing on international practices and their applicability to Uzbekistan. The study examines key instruments such as green bonds, climate funds, blended finance mechanisms, and public-private partnerships. It also evaluates the role of international financial institutions in supporting sustainable water infrastructure. Using a comparative analytical approach, the research identifies existing gaps in financing mechanisms and proposes policy directions for improving green investment flows in Uzbekistan’s water sector. The findings indicate that expanding green financial instruments can enhance infrastructure efficiency, reduce environmental risks, and improve long-term water security.